The decision to move: a theoretical model based on a case study (2009)
A displaced individual’s decision with respect to her new location is based on information from her social networks. This paper describes a possible displacement process for civilians. It focuses on the displacement events occurred in the Colombian Pacific south west –rural zone of Buenaventura and El Naya– at the peak of the paramilitary activity. By means of identifying standard patterns of threat, information sharing and displacement, it builds a social network model for the relocation of displaced people. An alternative explanation of the behaviour of those fleeing from war follows from the model above. The model focuses on two specific population groups within displaced people: natives and African descendants.